Red blood cell exchange in patients with sickle cell disease—indications and management: a review and consensus report by the therapeutic apheresis subsection of the AABB. Issue 8 (10th September 2018) - Biller, Elizabeth; Zhao, Yong; Berg, Mary; Boggio, Lisa; Capocelli, Kelley E.; Fang, Deanna C.; Koepsell, Scott; Music‐Aplenc, Lejla; Pham, Huy P.; Treml, Angela; Weiss, John; Wool, Geoffrey; et al.
Abstract : BACKGROUND: A prior practice survey revealed variations in the management of patients with sickle cell disease (SCD) and stressed the need for comprehensive guidelines. Here we discuss: 1) common indications for red blood cell exchange (RCE), 2) options for access, 3) how to prepare the red blood cells (RBCs) to be used for RCE, 4) target hemoglobin (Hb) and/or hematocrit (Hct) and HbS level, 5) RBC depletion/RCE, and 6) some complications that may ensue. STUDY DESIGN AND METHODS: Fifteen physicians actively practicing apheresis from 14 institutions representing different areas within the United States discussed how they manage RCE for patients with SCD. RESULTS: Simple transfusion is recommended to treat symptomatic anemia with Hb level of less than 9 g/dL. RCE is indicated to prevent or treat complications arising from the presence of HbS. The most important goals are reduction of HbS while also preventing hyperviscosity. The usual goals are a target HbS level of not more than 30% and Hct level of less than 30%. CONCLUSION: Although a consensus as to protocol details may not be possible, there are areas of agreement in the management of these patients, for example, that it is optimal to avoid hyperviscosity and iron overload, that a target Hb S level in the range of 30% is generally desirable, and that RCE as an acute treatment for pain crisis in the absence of other acute or chronic conditions is ordinarily discouraged.